Design of h¯-CPM-LFM Radar-Communication Integration Signal - Ye, Mingkun; Tang, Jun; Zhao, Yang; Su, Rongqing (Společnost pro radioelektronické inženýrství, 2022)
In light of the increasing requirement for the electromagnetic spectrum, the integration of radar and communication is widely concerned because of its equipment miniaturizing and high efficiency of spectrum. To address the issue that the communication information in integrated signals for radar and communication affects detection performance, A novel integrated signal is proposed in this paper. Inspired by the high communication efficiency of shaped octal phase-shift keying (S8PSK) and high spectral efficiency of the three-section integrated waveform k-LFM-CPM, we generate a new type of modulation ℎ¯-CPM by the introduction of a precoding method with low complexity and a time-varying modulation index h, h-CPM is used to encode communication data into LFM radar waveform to form a novel radar and communication integration waveform ℎ¯-CPM-LFM. Numerical results show that the designed waveform is at least 10 dB less spectrum extension than other integration waveforms when carrying large amounts of communication information and has excellent BER performance under the condition of strong out-of-band interference. Ambiguity function analysis shows that the waveform has excellent detection performance comparable to LFM.
Keywords: LFM; joint communication-radar; adaptive waveform design; ambiguity function; bit error rate (BER)